Safety evaluation of a strategy to restart elective orthopaedic surgery during the de-escalation phase of the COVID-19 pandemic. (1st August 2020) - Zahra, Wajiha; Dixon, Joseph W.; Mirtorabi, Negin; Rolton, Daniel J.; Tayton, Edward R.; Hale, Peter C.; Fisher, Warren J.; Barnes, Richard J.; Tunstill, Simon A.; Iyer, Shabnam; Pollard, Tom C. B.
Abstract : Aims: To evaluate safety outcomes and patient satisfaction of the re-introduction of elective orthopaedic surgery on 'green' (non-COVID-19) sites during the COVID-19 pandemic. Methods: A strategy consisting of phased relaxation of clinical comorbidity criteria was developed. Patients from the orthopaedic waiting list were selected according to these criteria and observed recommended preoperative isolation protocols. Surgery was performed at green sites (two local private hospitals) under the COVID-19 NHS contract. The first 100 consecutive patients that met the Phase 1 criteria and underwent surgery were included. In hospital and postoperative complications with specific enquiry as to development of COVID-19 symptoms or need and outcome for COVID-19 testing at 14 days and six weeks was recorded. Patient satisfaction was surveyed at 14 days postoperatively. Results: There were 54 females and 46 males (mean age 44 years, mean body mass index (BMI) 25.6 kg/m 2 ). In all, 56 patients underwent major orthopaedic procedures. There were no exclusions. One patient had a postoperative positive SARS-CoV-2 RT-PCR test but had no typical symptoms of COVID-19 infection and no clinical sequelae. 99% of patients were satisfied with the process and 98% would recommend undergoing elective orthopaedic surgery in the study period. Conclusion: In an environment with appropriate infrastructure, patient selection, isolation, screening, and testing, elective orthopaedic surgery is safe during the COVID-19 pandemic, and associated with high patient satisfaction. Further follow-up is required to establish that safety is maintained as the clinical restrictions are eased with the phased approach described. Cite this article: Bone Joint Open 2020;1-8:450–456.